Key Factors in Generation Z's Online Purchase Decision Making - Ridwan, Nurul Haeriyah; Musa, Chalid Imran; Haeruddin, M. Ikhwan Maulana (Asian Journal of Management Analytics, 2025)
The purpose of this study is to review the factors that trigger generation Z in making online purchasing decisions. researchers used a qualitative approach with phenomenological research methods. The key informants in this study were 10 students as a representation of generation Z. The data were collected using interviews, observation, and documentation. Data collection was carried out using interviews, observation, and documentation. The analysis technique in this study was assisted by using Nvivo 12 Pro. There are four stages in interpreting research data with the Nvivo Analysis test, namely: Import Data/Source Data, Coding Data, Project Visualization and Create Reports and Extracts.